Sistem Cek Harga Komoditas untuk Pemberdayaan Petani Polewali Mandar - Irfan AP; Musyrifah Musyrifah; Asmawati S; Adam M Tanniewa; Ainul Hayat H; Muhammad Zuhdi (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
This community service program aims to improve access to commodity price information for farmers and MSMEs in Polewali Mandar through the implementation of the Commodity Price Information System (SiCermat). The main problem addressed is limited access to price information, which weakens farmers’ bargaining position. The methods include socialization, training, technology implementation, mentoring, and participatory evaluation. The results indicate an improvement in participants’ ability to access price information, increased transparency in pricing, and greater confidence in marketing strategies. The program also contributes to distribution efficiency and potential income growth. Despite challenges such as limited internet access and varying levels of digital literacy, this program has strong potential to be developed as a digital-based farmer empowerment model.